PWE-029 Comparative assessment of the different management support programmes available to IBD patients at a DGH. (8th June 2018) - Johnson, Matt W; Wellsted, David; Pearce, Fiona M
Abstract : Introduction: Since 2012, a supported, self-help and management programme (SSHAMP) at the Luton and Dunstable University Hospital, has allowed over 950 IBD patients with stable symptoms to be managed safely within the community by encouraging self-management. IBD-SSHAMP is supported by consultants and specialist nurses through telephone clinics, relieving pressures on the hospital based outpatient clinic system. Both IBD-SSHAMP patients and those who continue to be under traditional hospital-based outpatient clinic care, also have access to online support via an IBD web-portal provided by Patients Know Best' (PKB). We were keen to see if the different forms of support provided differences in the perception of their disease control and health-related quality of life (HRQoL). Method: Between 2013 and January 2017, an estimated 575 patients had registered with PKB and 950 were on IBD-SSHAMP. A series of questionnaires were completed anonymously by 260 patients between January – July 2017. Measures included depression, anxiety, health-related quality of life, psychological flexibility and illness perception. Approximately 60% of patients completing the questionnaires receive traditional hospital outpatient care (n=158), with around 30% of those registered for additional online PKB support (n=46) comprising the PKB group and 70% (n=112) not registering for PKB and comprising the control (normal) care group. Of the 40% IBD-SSHAMP patients (n=101), 52% also registered for PKB (n=53) comprising the SSHAMP+PKB group. The remaining patients (n=48) were the SSHAMP only support group. Various univariate comparisons between the normal-care group and the 3 supported groups were undertaken as well as multivariate regression analysis. Results: In this patient cohort, women tended to responded more and there was a higher proportion of Crohn's disease in the females and compared to UC within the men. The proportion of men and women in the different patient groups was similar except that men were slightly over-represented in the normal (OPA)-care group and women in the SSHAMP+PKB group. Women had significantly lower HRQoL scores than men and scored worse on most psychological measures. CD diagnosis correlated with worse overall HRQoL and fatigue measures. The SSHAMP patient group had significantly better overall HRQoL and social-emotional HRQoL scores than the normal-care group. There were no significant psychological differences between PKB web-users and the normal-care group, although high PKB registration was observed amongst the SSHAMP group, particularly by younger female patients with Crohn's disease. Conclusion: High PKB registration by SSHAMP patients and lack of significant difference to the normal-care group by PKB users suggests that SSHAMP patients may be more engaged in their own care and that generally patients, especially women, are effective at seeking additional online support when needed. Psychological differences, including illness perceptions, appear to mediate the relationship between supportive care and HRQoL.